THE EFFECTIVENESS OF USING DUOLINGO ON STUDENTS’ VOCABULARY MASTERY AND WRITING COMPETENCE OF THE EIGHTH GRADE STUDENTS - Yuda Pradana, Wayan Radita; Ratminingsih, Ni Made; Ramendra, Dewa Putu (PRASI, 2023)
This study aimed to determine the effect of Duolingo on students' vocabulary mastery and writing competence, as well as the simultaneous effect on both. The population of this study was 8th-grade students of SMP Negeri 1 Singaraja in the academic year 2022/2023, totaling 329 students. The sample of this study involved 67 students, consisting of 34 students in the experimental group and 33 students in the control group. Multistage sampling was used as a sampling technique. Data were collected through a post-test covering writing competency tests and vocabulary tests. The data were analyzed using one-way MANOVA through the SPSS 22.0 application. The results showed that 1) there was a simultaneous effect of using Duolingo on students' vocabulary mastery and writing competence; 2) students who were taught using Duolingo showed better vocabulary mastery than those who were taught using conventional media; and 3) students who were taught using Duolingo showed better writing competence than those who were taught using conventional media. Thus, this study indicates that Duolingo enables students to acquire new vocabulary and master it so that their writing competence increases and motivates students to learn English in a fun way.